EFFECT OF POPULATION DYNAMICS ON ECONOMIC GROWTH IN TANZANIA: 1990-2022 - Dismas, Sanga; Arthur, Wainyaragania Kennedy; Timoth, Warioba Robby (International Journal of Research -GRANTHAALAYAH, 2023)
The study analysed the correlation between population dynamics and economic expansion in Tanzania using time series information covering from 1990 - 2022. The study was influenced by persistent population growth in the country. Comprehending this matter will offer a dependable basis for formulating development policies. The author sought to determine the effect of crude birth rate, crude death rate and net migration on her economic growth. VECM was employed for estimation. Stationarity test results demonstrated that variables became stationary after being differentiated twice and cointegration test results detected that the variables were cointegrated at rank 5 which compelled the use of the Vector Error Correction Model (VECM). The VECM findings showed that the long-term expansion of the economy is significantly affected by population dynamics. Moreover, crude birth rate positively affects economic growth while crude death rate and net migration negatively affect economic growth. The study recommends that the government should control the outflow of Tanzanians to other countries to avoid loss of human resources, the government is supposed to pump in more resources on the health sector to minimize and delay mortalities thus increasing output growth and the government must ensure that birth rate is controlled although it is positively related with economic growth, precaution must be observed.